The Decrease In Ammonia Effluent Tss And Rubber With A Combination Of Anaerobic Biofilter Media And Phytoremediation For Live Fish - Putri, Dewinta Nulan; Hasbi, M; ', Budijono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
Research was conducted on Desember 2013 until february 2014 at rubber factory (RICKY) in Meranti Pandak district Rumbai-Pekanbaru City on Riau Province. Analysis waste water parameters was done in laboratory Ekologi and Management faculty marine environment, fisheries and merine science Pekanbaru-Riau Province. Method used in research to experiment without design combined with experiment of media biofilter plant plastic bottle with water to lower value of TSS and Ammonia to be testing treated effluent to fish. One reactor to fitoremidiasi with one reactor plants and without plants as controls fitoremidiasi. TSS and decrease Effectiveness of ammonia in waste water rubber anaerobic biofilter process mediated combination with phytoremediation plastic bottles 89,90% during 92,82% study ranged from average effectiveness is 91,18%. Where, average TSS levels at outlet during observation 144.13 mg/1. While, average for ammonia effectiveness decline reached 88.23%, with average ammonia concentration in outlet of 2.06 mg/1. Thus parameters for TSS and Ammonia has been completed with environment minister’s decision number Kep 51/MENLH/10/1995 effluent quality standard for rubber industry is to ammonia content and latexs is a total wasted of 15 mg/1 and for waste rubber dry form by 5 mg/1. While support for parameters such as Ph, DO, and temperature have appropriate quality standard recommended for rubber industry, and able to support fish life during test observations.Keywords : Total Suspended Solid, Ammonia, waste water, biofilter, plastic bottle, Water hyacinth